Development of Drum-Buffer-Rope scheduling software to support a “what if” approach to scheduling job shops - De Jager, C. J. (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MScEng (Industrial Engineering))--University of Stellenbosch, 2006.